Growth and total carotenoid, chlorophyll a and chlorophyll b of tropical microalgae (Isochrysis sp.) in laboratory cultured conditions - Khan Chowdhury, Ahmed Jalal; Shamsudin, A.A; Rahman, M.F; Nurzatul , N.Z; Rozihan, M (Asian Network for Scientific Information, 2013)
A study was conducted to determine the total content of carotenoids, in Isochrysis sp. under stress condition (nitrogen starvation). Isochrysis sp. was cultured in f/2 medium at optimum light intensity (1200 Lux) with constant aeration (4.5 L min-1) at 8 pH. Salinity of the water was maintained between 20-24 g L-1 and temperature range was 20-24°C. The culture of Isochrysis sp. showed a short lag phase lasting about 24 h followed by exponential phase starting from day 2 until day 10. In day 4, specific growth rate (u.) for Isochrysis sp. was 1.6059 day-1, the highest rate compared to other day. Stress parameter (NO- 3 starvation) was introduced into the mass culture on day 4 by eliminating NO- 3~ in f/2 media. There was considerable declining (p<0.05) in cell count was observed in the absence of nitrogen proving the dependency of carotenoid production over the nitrogen limitation which probably due to the main role played by the nitrogen in various metabolic activities of the cell. The highest total carotenoid per cell was recorded at day 10 with 0.001932347 mg mL-1, whereas the lowest total carotenoid content per cell was observed at day 4 with 0.000100649 mg mL-1. The finding reveals that it is best to harvest the carotenoid on day 10, when the maximum carotenoid can be obtained. © 2013 Asian Network for Scientific Information.